Financialisation and the potentials for a progressive equality-, sustainability- and domestic demand-led regime: A post-Keynesian simulation approach - Eckhard Hein; Franz Prante; Alessandro Bramucci (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2022)
In several publications, starting more than a decade ago, Peter Flaschel and co-authors have outlined the features of a 'social capitalism' as a normative alternative to the liberal and financialised capitalism of the Anglo-Saxon type, but also to the undemocratic Chinese-type of state capitalism. Theoretically and analytically, this concept has been built on a MarxKeynes/Kalecki-Schumpeter approach to macroeconomics. Our approach in this paper, based on post-Keynesian/Kaleckian foundations and making use of a two-country stock-flow consistent (SFC) simulation model, shares with Flaschel and co-authors the search for an alternative to the liberal finance-dominated capitalism which has dominated, to different degrees in different countries, since the late 1970s/early 1980s and led to the 2007-09 crises. On the one hand, our approach is narrower than the one by Flaschel and co-authors, since we are explicitly in our model only focusing on demand and growth regimes, as well as on macroeconomic policy regimes, but only implicitly on innovations and structural change. On the other hand, however, we shed light on different regimes in modern capitalism, their interaction at the global scale, and then on the changes in regimes after the 2007-09 crises. Finally, we present the main features of a progressive and more stable equality-, sustainability- and domestic demand-led regime. We believe that such a progressive regime is in the spirit of Flaschel and co-authors' concept of 'social capitalism', but we also point out some disagreements regarding the underlying model and the core policies.
Keywords: B59; E02; E11; E12; E25; E65; F41; O41; 330; post-Keynesian macroeconomics; financialisation; growth regimes; inequality; debt; social capitalism; stock-flow consistent model